Genetic risk factors for anterior cruciate ligament ruptures: COL1A1 gene variant. Issue 5 (4th February 2009) - Posthumus, M; September, A V; Keegan, M; O'Cuinneagain, D; Van der Merwe, W; Schwellnus, M P; Collins, M
Abstract : Background: Anterior cruciate ligament (ACL) ruptures are considered the most severe injury sustained in sports. Although various intrinsic and extrinsic risk factors have been identified, the exact aetiology of the injury is not yet fully understood. Recently, the gene encoding for the α1 chain of type I collagen ( COL1A1 ) has been shown to be associated with cruciate ligament ruptures and shoulder dislocations. Objective: To determine whether the functional Sp1 binding site polymorphism within intron 1 of the COL1A1 gene is associated specifically with ACL ruptures in an independent population. Methods: 117 Caucasian participants with surgically diagnosed ACL ruptures, and 130 Caucasian physically active controls without any history of previous ligament or tendon injuries were recruited for this case–control genetic association study. All participants were genotyped for the COL1A1 Sp1 binding site polymorphism (G/T; rs1800012). Results: The rare TT genotype was significantly (p = 0.031, OR = 0.08, 95% CI <0.01 to 1.46) under-represented in the ACL group (0 out of 117, 0%), compared with the controls (6 out of 130, 4.6%). Conclusion: The TT genotype of the COL1A1 Sp1 binding site polymorphism was significantly under-represented in South African participants with ACL ruptures. We propose that this sequence variant be the first specific genetic element to be included in multifactorial models developed to understand the aetiology and risk factors for ACL rupture.